Preparation of TiO2 and WO3–TiO2 nanotubes decorated with PbO nanoparticles by chemical bath deposition process: A stable and efficient photo catalyst - Momeni, Mohamad Mohsen; Nazari, Zohre (Ceramics international, 2016)
We present a new method for synthesizing Pb/TNTs and Pb/WTNTs composite with good photo catalytic activity. TiO2 nanotube (TNTs) and WO3–TiO2 nanotubes (WTNTs) were prepared by one-step electrochemical anodizing method and lead has been successfully deposited on these nanotubes by chemical bath deposition process. The morphology, crystal structure, elemental composition and light absorption capability of the prepared samples were evaluated using various characterization techniques. Results showed that the fabricated films have highly ordered nanotube morphology. Diffuse reflectance spectra showed an increase in the visible absorption relative to bare samples. The degradation of methylene blue was used as a model reaction to evaluate the photo catalytic activity of these novel visible-light-responsive photo catalysts. Results showed that the photo catalytic activity of bare WTNTs samples is higher than that with undoped TNTs sample. Compared with unmodified TNTs and WTNTs, the Pb/TNTs and Pb/WTNTs samples exhibited enhanced photo catalytic activity in the degradation of methylene blue. The sample Pb/WTNTs exhibited better photo catalytic activity than other samples. Also prepared photo catalysts showed good stability and could be recycled several times without significant loss of their activity. This work provides an insight in designing and synthesizing new WTNTs-based hybrid materials for effective visible light-activated photo catalysis. Since Pb/TNTs and Pb/WTNTs electrodes can be easily removed and replaced after the photo catalytic reaction, avoiding the filtration step after photoreaction or the immobilizing process required for photo catalyst particles, the operation in the photo-reactor becomes much easier from an engineering point of view. The catalysts prepared in this study exhibit industrially relevant interests due to the low cost and high photo catalytic activity.